Feasibility of totally laparoscopic pylorus-preserving gastrectomy with intracorporeal gastro-gastrostomy for early gastric cancer: a retrospective cohort study - Akiyama, Yuji (World J Surg Oncol, 2020)
BACKGROUND: Pylorus-preserving gastrectomy (PPG) has been accepted as a function-preserving surgery for the treatment of early gastric cancer in East Asian countries. Therefore, this study aimed to evaluate the feasibility and safety of totally laparoscopic PPG (TLPPG) with intracorporeal anastomosis. METHODS: A total of 43 patients with early gastric cancer underwent laparoscopy-assisted PPG (LAPPG) with extracorporeal anastomosis between May 2006 and November 2012. The operative outcomes of 22 patients who underwent TLPPG between November 2012 and February 2019 were evaluated, and data were compared with that of the LAPPG group. RESULTS: No significant difference in the operative time was observed between the two groups. Blood loss was lower in the TLPPG group (18.5 mL) than in the LAPPG group (30.7 mL, p = 0.008), and the length of abdominal incision was shorter in the TLPPG group (3.8 cm) than in the LAPPG group (4.7 cm, p < 0.001). No significant difference in the complication rate was observed between the two groups (13.6% in the TLPPG vs. 9.3% in the LAPPG group, p = 0.594). No anastomosis-related complications occurred in either group. No significant between-group difference was observed in the delayed gastric emptying (TLPPG, 9.1 vs. LAPPG, 7%, p = 0.762). The initiation of postoperative fluid (TLPPG, 1.0 day vs. LAPPG, 3.0 days, p < 0.001) and meal (TLPPG, 3.0 days vs. LAPPG, 4.0 days, p < 0.001) intake was earlier in the TLPPG group than in the LAPPG group. No significant between-group difference was observed in the postoperative hospital stay. CONCLUSIONS: The findings of this study suggest that TLPPG with intracorporeal reconstruction not only is as feasible and safe as LAPPG for the treatment of patients with early gastric cancer but also provides certain advantages such as reduced blood loss and wound size.